Paper and paperboards in India : demand forecasts and policy implications - Gupta, Tirath R.; Shah, Nitin; Indian Institute of Management, Ahmedabad (New Delhi : Oxford & IBH Pub. Co., 1987)
Study based on 1960-1985 data.
Study conducted by the Indian Institute of Management, Ahmedabad.
Includes bibliographical references (p. [86]-91).
Amirul
Keywords: Paper industry -- India -- Forecasting; Paperboard industry -- India -- Forecasting